2021
DOI: 10.1029/2020jf005761
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Differential Ablation and Dynamic Detachment in Driving Accelerating Mass Loss From a Debris‐Covered Himalayan Glacier

Abstract: Supraglacial rock debris is present on 7% of the global mountain glacier area, dramatically affecting the sensitivity of these glaciers to climate change (Herreid & Pellicciotti, 2020). Debris-covered ice represents 30% of the glacier mass in ablation areas in High Mountain Asia (Kraaijenbrink et al., 2017). Supraglacial debris in the Everest region is typically sufficiently thick to reduce ablation by insulating the underlying ice surface (Nicholson & Benn, 2013). As a result, these debris-covered glaciers ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 72 publications
0
27
0
3
Order By: Relevance
“…The glacier response times were shorter than the intervals of 0.6–2.0 kyr between phases of moraine construction (Table 2). The dynamic response time of Khumbu Glacier to the change in mean annual air temperature between the LIA and the present day was quantified using numerical modeling as 200–300 years (Rowan et al., 2021) and for Lobuche Glacier this will be shorter due to its relatively small size and steep slope (Oerlemans, 1989). Therefore, we suggest that the difference in the number of glacial stages represented at Khumbu and Lobuche Glaciers is the result of the superimposition of sediment that has buried some older moraine crests.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The glacier response times were shorter than the intervals of 0.6–2.0 kyr between phases of moraine construction (Table 2). The dynamic response time of Khumbu Glacier to the change in mean annual air temperature between the LIA and the present day was quantified using numerical modeling as 200–300 years (Rowan et al., 2021) and for Lobuche Glacier this will be shorter due to its relatively small size and steep slope (Oerlemans, 1989). Therefore, we suggest that the difference in the number of glacial stages represented at Khumbu and Lobuche Glaciers is the result of the superimposition of sediment that has buried some older moraine crests.…”
Section: Discussionmentioning
confidence: 99%
“…The equilibrium line altitude of debris-covered glaciers is difficult to infer from their geometry, as heavily debris mantled termini persist at lower elevations than would be possible for climatically equivalent clean-ice glaciers, but is estimated from numerical modeling as being above 6,000 m a.s.l. (Rowan et al, 2021). (Finkel et al, 2003;Richards, 2000;Richards et al, 2000;Rowan, 2017).…”
Section: Field Sitementioning
confidence: 99%
See 1 more Smart Citation
“…They revealed that the tongue area showed a considerable dh (-2.81 m) during an ablation period and that its dynamic state is very weak, similar to what we observe for 23K Glacier. Other studies concerning the mass balance of Himalayan debris-covered glaciers also report on glaciers which possess a high dh rate (~-0.9-1.8 m a -1 ) and weaker dynamic state (Vincent et al, 2016;Nuimura et al, 2017;Brun et al, 2018;Rowan et al, 2021), and which possess dh patterns which are consistent with that of 23K Glacier. In summary, the dh pattern for 23K Glacier appears to conform to that of other Himalayan debris-covered glaciers, whilst that of 24K Glacier is exceptional is perhaps more anomalous.…”
Section: Controls Of the Dh Patternsmentioning
confidence: 94%
“…Although the employed parameters are a good compromise for large-scale applications (Maussion et al, 2019), they may lead to overestimated ice volume (Farinotti et al, 2019a). Debris cover on glaciers, which considerably influences glacier mass balance (Rounce et al, 2021), is often investigated at a local scale (Anderson and Anderson, 2018;Rowan et al, 2021) and has only recently been incorporated into a global glacier model (GloGEM, Compagno et al, 2021). Because debris cover can both accelerate and reduce ice loss, we cannot comment at this point on the extent to which debris cover will influence glacial lake formation in HMA in the 21st century.…”
Section: Uncertainty Assessment and Data Qualitymentioning
confidence: 99%